Identification of placebo responsive participants in 40km laboratory cycling performance - Beedie, C. J.; Foad, A. J.; Coleman, D. A. (Journal of Sports Science & Medicine, 2008)
The placebo effect, a positive outcome resulting from the belief that a beneficial treatment has been received, is widely acknowledged but little understood. It has been suggested that placebo responsiveness, the degree to which an individual will respond to a placebo, might vary in the population. The study aimed to identify placebo-responsive participants from a previously published paper that examined the effects of caffeine and placebos on cycling performance. A quantitative model of placebo responsiveness was defined. 14 male participants were subsequently classified as either placebo responsive or non-responsive. Interviews were conducted to corroborate these classifications. Secondary quantitative analyses of performance data were conducted to identify further placebo responses. Finally, the five factor model of personality was used to explore relationships between personality and placebo responsiveness. Overall, 5 of 14 participants were classified as placebo responsive. Performance data suggested that 2 participants were placebo responsive whilst 12 were not. Interview data corroborated experimental data for these participants and for 9 of the remainder, however it suggested that the remaining 3 had experienced placebo effects. Secondary quantitative analysis revealed that performance for these 3 participants, whilst no better than for non-responsive participants, was associated with substantially increased oxygen uptake in the 2 conditions in which participants believed caffeine had been administered (7.0% ± 15.1; 95% confidence intervals -2.6 to 16.7, and 6.0% ± 15.4; -3.9 to 15.9 respectively). Finally, data suggested that the personality factors of extroversion, agreeableness, openness and neuroticism may relate to placebo responding. Placebo effects such as pain tolerance and fatigue resistance might be experienced by a percentage of participants but might not always be manifest in objective measures of performance.